Moisture Sorption Characteristics of Dehydrated in-shell African Walnut (Tetracarpidium conophorum) - Ezekiel, O. O.; Olurin, T. O.; Akomolafe, A. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2018)
Moisture sorption isotherms are useful thermodynamic tools for determining water interactions within food systems and providing information that can assist in optimizing food processing operations such as drying, mixing, packaging and storage, as well as to maximize retention of quality parameters such as colour, aroma, texture, and nutrient. Moisture sorption isotherm characteristics of African walnut were evaluated at three different temperatures (28, 33 and 38°C) and relative humidity range of 11.20 - 97.00 % using gravimetric method; five mathematical models (GAB, BET, Peleg, Smith and Ferro Fontan) were fitted into the experimental data. Sorption isotherms of the dehydrated walnut gave type II (S-shaped) isotherms according to BET classification. Temperature had significant effect on the equilibrium moisture content (EMC). A nonlinear regression analysis method was used to evaluate the constants of sorption models. The models were evaluated statistically by calculating coefficient of determination (R2), the mean relative percentage error (P) and the reduced chi-square (λ2). The BET model gave the best fit for the obtained data among the tested models with R2 value of 0.9892. Calculated monolayer moisture (Mo) content from BET ranged from 5.018 to 7.922% db for adsorption and 9.842 to 10.143% db for desorption respectively.